The constitutional rights of children: in re Gault and juvenile justice - Tanenhaus, David Spinoza (Landmark law cases & American society)
A disgrace for the state of Arizona -- Have you got big bombers? -- This is going to be a great case -- It will be known as the Magna Carta for juveniles -- Kent and Gault already seem like period pieces